PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH TERHADAP MOTIVASI KERJA GURU DI SMP AL-WASHLIYAH 5 HAMPARAN PERAK - Ariana; Rahmatun Nisa; Fikri Hamdi Siregar; Abdul Fattah Nasution (PT PUBLIKASI INSPIRASI INDONESIA, 2026)
This study aims to analyze the influence of the principal’s leadership style on teachers’ work motivation at SMP Al-Washliyah 5 Hamparan Perak. The principal’s leadership plays a strategic role in directing, motivating, and creating a conducive working environment to support teachers in performing their professional duties effectively. Teachers’ work motivation is a crucial factor affecting their performance, commitment, and professionalism in the teaching and learning process. This research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to teachers as respondents and analyzed using inferential statistical techniques. The results indicate that the principal’s leadership style has a significant effect on teachers’ work motivation. These findings suggest that the more effective the leadership style applied by the principal, the higher the level of teachers’ work motivation in carrying out their responsibilities. Therefore, principals are expected to implement appropriate, participative, and human-resource-oriented leadership styles to enhance teachers’ motivation and improve the quality of education in schools.